В решении.
Объяснение:
Подставить известное значение n в уравнение и вычислить k:
k = 4n -11
n=5 k=4 * 5 - 11 = 9;
n=3 k=4 * 3 - 11 = 1;
n=1 k=4 * 1 - 11 = -7;
n=0 k=4 * 0 - 11 = -11;
n= -2 k=4 * (-2) - 11 = -8 - 11 = -19;
n= -6 k=4 * (-6) - 11 = -24 - 11 = -35.
Таблица:
n 5 3 1 0 -2 -6
k 9 1 -7 -11 -19 -35.
В решении.
Объяснение:
Подставить известное значение n в уравнение и вычислить k:
k = 4n -11
n=5 k=4 * 5 - 11 = 9;
n=3 k=4 * 3 - 11 = 1;
n=1 k=4 * 1 - 11 = -7;
n=0 k=4 * 0 - 11 = -11;
n= -2 k=4 * (-2) - 11 = -8 - 11 = -19;
n= -6 k=4 * (-6) - 11 = -24 - 11 = -35.
Таблица:
n 5 3 1 0 -2 -6
k 9 1 -7 -11 -19 -35.